CHARACTERIZATION OF THE SMALL RUMINANT VALUE CHAIN IN THE MEDITERRANEAN: THE CASE OF THE NORTHERN JORDAN - Rula Awad; Hosam Titi; Aziza Mohamed-Brahmi; Mohamed Jaouad; Aziza Gasmi-Boubaker (Journal of Animal and Plant Sciences, 2024)
The objective of this study was to characterize the small ruminant value chain in the Northern Jordan, map out its stakeholders and their roles, and identify the challenges facing it in order to improve its production efficiency and ensure its sustainability. Data were obtained from a sampling survey of 134 small ruminant holders located in the Northern region of Jordan. The survey focused on the main aspects of small ruminant production as input supplies, husbandry practices, processing, marketing, and consumption. Also, individual semi-structured interviews of 20 animal health care suppliers, 25 dairy processors, 25 butchers, and 20 traders, were used to undertake small ruminant value chain analysis. The results showed that the small ruminant value chain in the study area involved multiple actors with diverse roles represented by input suppliers, producers, traders, processors, and consumers. Present findings indicated that the value chain associated with small ruminants is primarily limited by the spatial constraints posed by the expansion of urban areas into rangeland regions, government policies concerning the management of forested areas, as well as the cultivation and afforestation of privately owned land. Additionally, the high production costs coupled with low milk prices and competition of imported meats, and production management also contributed to the constraints in the value chain. Based on these findings, it can be concluded that the small ruminant value chain is poorly organized and lack strong interconnections among its stakeholders. Therefore, there is a clear necessity to establish effective linkages between all stakeholders involved in the small ruminant value chain within the study area. Furthermore, addressing the weaknesses and threats identified within this sector is first step in order to enhance the production and marketing of small ruminants.
Keywords: Small ruminant; Value chain; Mediterranean; The Northern regions; Jordan